A tetraphenylethylene-based covalent organic framework for waste gas adsorption and highly selective detection of Fe3+. Issue 33 (13th August 2021) - Cui, Di; Ding, Xuesong; Xie, Wei; Xu, Guangjuan; Su, Zhongmin; Xu, Yanhong; Xie, Yuzhong
Abstract : A tetraphenylethylene-based covalent organic framework shows an outstanding performance for waste gas adsorption and has good selectivity and detection effect for Fe 3+ . Abstract : A tetraphenylethylene-based covalent organic framework (TTPE-COF) with a rhomboid-shaped framework is constructed by a Schiff base reaction. Due to its porous structure and high surface area (681.27 m 2 g −1 ), the TTPE-COF will be a meritorious adsorbent for gas storage (CO2 of 485.89 mg g −1 at 45 bar/318 K) and volatile organic compound (VOC) capture (benzene of 5.80 mmol g −1 and toluene of 5.20 mmol g −1 at 293 K). Furthermore, the TTPE-COF has good selectivity and detection effect for Fe 3+, and the detection limit (LOD) of Fe 3+ is 3.07 μM. The TTPE-COF has potential applications in adsorbents and fluorescent sensors.